Aminosilane as an effective binder for hydroxyapatite-gelatin nanocomposites - Luo, Tzy-Jiun M. (2010)
Aminosilane has been explored as an alternative chemical linker to facilitate the binding and solidification of hydroxyapatite-gelatin nanocomposite at room temperature, which was synthesized using co-precipitation method in the presence of gelatin. This aminosilane treatment was found effective at low concentration (~25 μL/mL) and the solidification and dehydration of hydroxyapatite-gelatin slurry completes within hours depending on the amount of aminosilane. The resulting sample exhibits compressive strength of 133 MPa, about 40% higher than glutaraldehyde treated samples, and shows good biocompatibility based on cell adhesion, proliferation, alkaline phosphate synthesis, and mineralization studies.